2009
DOI: 10.1021/es803695n
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Polychaete and Polyethylene Uptake to Assess Sediment Resuspension Effects on PCB Bioavailability

Abstract: Polyethylene sampler uptake was compared to polychaete uptake to assess bioavailability of polychlorinated biphenyls (PCBs) from resuspended sediments. New Bedford Harbor (MA, U.S.) sediment contaminated with PCBs, was resuspended under four different water column oxidation conditions: resuspension alone, resuspension under aeration, resuspension under helium, and no resuspension (control). Residuals were tested for differences in PCB availability to the marine polychaete Nereis virens and to polyethylene (PE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 42 publications
5
71
2
Order By: Relevance
“…Polymer-coated (such as poly(dimethyl)siloxane [PDMS]) glass fibers [10] and low-density polyethylene (LDPE) films [11] have been used as biomimic probes, because they behave similarly to biological lipid. In such applications, the key step is to accurately determine the partition coefficients between the sorbent phase and water.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-coated (such as poly(dimethyl)siloxane [PDMS]) glass fibers [10] and low-density polyethylene (LDPE) films [11] have been used as biomimic probes, because they behave similarly to biological lipid. In such applications, the key step is to accurately determine the partition coefficients between the sorbent phase and water.…”
Section: Introductionmentioning
confidence: 99%
“…Available information [2,3,9] shows that, so far, harbors have been selected most widely for sediment porewater sampling, so the partitioning of target analytes between sediment porewater and the sorbent phase could be impacted by dissolved salt. Adams et al [24] found that the partition coefficients of phenanthrene and pyrene between LDPE and freshwater were approximately 94% of those obtained with 0.1 M NaCl solution instead of freshwater, but the deviation could be corrected with the Setschenow constant [25].…”
Section: Salinitymentioning
confidence: 99%
“…It has been shown to be able to accumulate HOCs with high partition coefficients, and developed into the sorbent phase used in polyethylene devices (PEDs). These PEDs have been used to measure dissolved HOC levels in sediment porewater [3,8,9] and to assess the effects of sediment resuspension on the bioavailability of PCBs [9] (Table 1). Thin LDPE sheets are cheap (US$0.40/m 2 ) [34], firm, easily deployable in sediment, and scalable to various sensitivity needs, so they are ideal for monitoring dissolved HOC levels in sediment porewater.…”
Section: Benefits and Shortfalls Of Available Passive Sampling Technimentioning
confidence: 99%
See 2 more Smart Citations